2023
DOI: 10.1007/s00402-023-04847-5
|View full text |Cite
|
Sign up to set email alerts
|

Does access through the pronator quadratus influence pronation strength in palmar plate fixation of distal radius fractures in elderly patients?

Abstract: Introduction Palmar plate fixation of the distal radius fracture involves dissecting the pronator quadratus (PQ). This is regardless of whether the approach is radial or ulnar to the flexor carpi radialis (FCR) tendon. It is not yet clear whether and to what extent this dissection leads to a functional loss of pronation or pronation strength. The aim of this study was to investigate the functional recovery of pronation and pronation strength after dissection of the PQ without suturing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Given that the pronator quadratus functions as a secondary forearm pronator and dynamically stabilizes the distal radioulnar joint, and an intact pronator quadratus can serve as a biological barrier for the flexor tendons, the question of whether the integrity or repair of the pronator quadratus contributes to clinical outcomes is a frequently debated topic [22][23][24]. Despite diverse perspectives in the literature [25][26][27][28], current high-level evidence suggests that the integrity or repair of the pronator quadratus does not definitively impact clinical results [22][23][24]29]. In our clinical practice, displaced fractures of the distal radius often coincide with a partial tear of the pronator quadratus.…”
Section: Screw Insertionmentioning
confidence: 99%
“…Given that the pronator quadratus functions as a secondary forearm pronator and dynamically stabilizes the distal radioulnar joint, and an intact pronator quadratus can serve as a biological barrier for the flexor tendons, the question of whether the integrity or repair of the pronator quadratus contributes to clinical outcomes is a frequently debated topic [22][23][24]. Despite diverse perspectives in the literature [25][26][27][28], current high-level evidence suggests that the integrity or repair of the pronator quadratus does not definitively impact clinical results [22][23][24]29]. In our clinical practice, displaced fractures of the distal radius often coincide with a partial tear of the pronator quadratus.…”
Section: Screw Insertionmentioning
confidence: 99%
“…Nguyen et al found that a hand strength-focused exercise program for elderly DRFs non-surgically managed with CI while significantly immobilized improves grip strength [76]. VLPF involving dissecting the pronator quadratus significantly lowers range of motion and pronation strength [77], so post-surgical rehabilitation might be beneficial. Nonetheless, Gamo et al found that hand therapies improve the outcomes after VLPF for DRFs in middle-aged to elderly women at 8 weeks but not at 6 months after surgery [78].…”
Section: Post-treatment Rehabilitationmentioning
confidence: 99%